Prognosis of Syncope With Head Injury: a Tertiary Center Perspective - Furtan, Stanisław; Pochciał, Paweł; Timler, Dariusz; Ricci, Fabrizio; Sutton, Richard; Fedorowski, Artur; Zyśko, Dorota (Frontiers in Cardiovascular Medicine, 2020)
Aim: Head injury is the most common trauma occurring during syncope. We aimed to assess whether syncope as cause of head-trauma affects short-and long-term prognosis. Methods: From a database retrospective analysis of 97,014 individuals attending Emergency Department (ED), we collected data of patients with traumatic head injury including age, gender, injury mechanism, brain imaging, polytrauma, bone fracture, intracranial bleeding, and mortality. Mean follow-up was 6.4±1.8 years. Outcome data were obtained from a digital national population register. The study population included 3470 ED patients with head injury: 117 patients (50.0±23.6 years, 42.7% men) who reported syncope as trauma etiology, and 3315 patients (32.2±21.1years, 68.5% men) without syncope preceding head trauma. Results: Thirty-day mortality was low and similar in traumatic head injury with or without syncope. One-year and long-term all-cause mortality were both significantly higher in syncopal versus non-syncopal traumatic head injury (11.1% vs 2.8% and 32% vs 10.2%, respectively; both p<0.001). In adjusted logistic regression analysis, death between 121st-day and 1-year in patients with head-trauma was associated with male gender (odds ratio (OR): 6.48; 95% CI: 2.59-16.25), advancing age (per year) (OR 1.09; 95% CI 1.07-1.11), Glasgow Coma Scale<13 (OR: 6.18; 95% CI:1.68-22.8), bone fracture (OR 4.72; 95% CI 2.13-10.5), and syncope (OR 3.70; 95% CI: 1;48-9.31). In multivariable Cox regression analysis, syncope was one of the strongest independent predictors of long-term all-cause death (hazard ratio: 1.95; 95% CI 1.37-2.78). Conclusion: In patients with head trauma, history of syncope preceding injury does not increase 30-day all-cause mortality but portends increased one-year and long-term mortality.